The Seasonally Altered Atmosphere Moisture Circulations With Rainfall and Rainfall Isotopes in Southwest China - Zhao, Jingyao; Tan, Liangcheng; Li, Dong; Pérez-Mejías, Carlos; Dong, Xiyu; Wang, Jian; Zhang, Haiwei; Cheng, Hai (Frontiers in Earth Science, 2022)
To interpret the climatic signals of precipitation/speleothem δ18O, it’s critical to identify the importance of the factors affecting the precipitation δ18O. This study presents new stable isotope data for precipitation δ18O and δD in the site of Shenqi cave, southwest China, from November-2015 to October-2016 (the ‘Super-El Niño’ event), to investigate the regional-scale climate forcing on precipitation δ18O. The precipitation δ18O, δD and d-excess have an obvious seasonality, relatively low values in the wet season and high in the dry season. The further analysis of seasonally altered LMWL and moisture circulations suggested that changes in atmosphere moisture circulations would be the key factor underlying the precipitation/speleothem δ18O fluctuations in our study area at least on seasonal timescales. Combined with the seasonal-monthly variations of the IsoGSM δ18O, GPCP/CRU rainfall and NCEP/NCAR moisture fluxes, we detected that the super-El Niño of 2016 have changed the distributions of monthly rainfall in wet season through the Western Pacific Subtropical High, but not mainly the precipitation isotopic compositions and moisture circulations in our study area.